INDIAN AND PAKISTANI REGIME TRAJECTORIES: SOCIAL HIERARCHY AND MAJORITY RELIGION’S PUBLIC PRESENCE VERSUS DEMOCRACY - Nitza-Makowska, Agnieszka (Politikologija religije, 2020)
The hierarchical organisation of society and the lack of distinction between the public and private sphere in Islam and Hinduism are cultural features of India and Pakistan that seem inconsistent with democracy. Reservation policy and the recognition of the most popular regional languages both demonstrate the adjustment of India’s democratic framework to the caste system and the arithmetic of ethnic groups respectively. These measures have helped to pave the way for India's smooth political transition. In contrast to the Indian National Congress, the Muslim League refused to introduce similar solutions in Pakistan. The public presence of Hinduism in India and Islam in Pakistan have barely affected the countries overall political trajectories. However, the recent radicalisation, marked by the rise of the Bharatiya Janata Party in India and the emergence of the Islamist political movements, including the Tehreek-e-Labbaik Party in Pakistan, have triggered tendencies towards authoritarianism. This paper concludes by reconsidering the similarities between the impact of the majority religion’s public presence on the post-2014 Indian and Pakistani regime trajectories. By the comparative analysis of the two countries, this study contributes to the contemporary debates in political sciences about the rise of authoritarianism and the demand for identity.